Anti-continuum approach on nonlinear localized modes in dipolar Bose-Einstein condensates in optical lattice - Badarudin, M. H.; Hadi, Morteza S.A.; Umarov, Bakhram A. (IOP Publishing Ltd., 2017)
This paper aims to analyze the stability of nonlinear localized modes in dipolar Bose-Einstein condensates in optical lattice by anti-continuum approach. It is relatively convenient to employ the anti-continuum method for solving discrete nonlinear Schrödinger equation. This method has shown the ability to produce similar result of analysis of the system stability as produced by other methods. The dynamical stability of the system has been investigated within certain permissible range of parameters.